Galveosaurus herreroi, a new sauropod dinosaur from Villar del Arzobispo Formation (Tithonian-Berriasian) of Spain - Sánchez-Hernández, Bárbara (Zootaxa, 2005)
The Galve fossil sites (province of Teruel, Spain) have provided many Mesozoic vertebrate remains. Among these are isolated sauropod dinosaur bones, including one taxon reported only from this locality, Aragosaurus ischiaticus. Here, a new species is named from the Tithonian deposits of the Villar del Arzobispo Formation, of Galve (Teruel province, Spain), Galveosaurus herreroi gen. et sp. nov. It is represented by two humeri, one sternal plate, one ischium, one scapula, one cervical vertebra, one caudal dorsal vertebra, five caudal vertebrae, one Y-shaped chevron and some fragments of ribs. This new species is an eusauropod dinosaur that shows primitive features such as a slightly curved ischium with an unexpanded distal end, amphicoelous vertebrae, neural spine not bifid and an unforked chevron. It appears to be closer to cetiosaurid genera such as Barapasaurus or Cetiosaurus. This new basal sauropod lived at the same time as the eusauropod Lourinhasaurus alenquerensis from Portugal. These are both relict genera that survived in the Iberian Peninsula when more derived neosauropods, such as Losillasaurus or Dinheirosaurus, had taken over other parts of Iberia.